2020
DOI: 10.1186/s12889-020-08928-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with musculoskeletal symptoms and heart rate variability among cleaners – cross-sectional study

Abstract: Background: The professionals who perform cleaning activity constitute a major economic sector in Brazil. Cleaners may develop health problems related to the musculoskeletal and cardiovascular systems. It is necessary to understand the working and health conditions of cleaners in Brazil. Thus, the aim of this study was to identify factors associated with musculoskeletal symptoms and heart rate variability (HRV) among cleaners. Methods: A cross-sectional study conducted at a public higher education institution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In an American study on hotel housekeepers, 21% of them met the criteria for high blood pressure, 36 with values close to the ones obtained in our study. A Brazilian study 37 carried out on 45 cleaning workers to evaluate musculoskeletal disorders found a prevalence of arterial hypertension of 23%, also very similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…In an American study on hotel housekeepers, 21% of them met the criteria for high blood pressure, 36 with values close to the ones obtained in our study. A Brazilian study 37 carried out on 45 cleaning workers to evaluate musculoskeletal disorders found a prevalence of arterial hypertension of 23%, also very similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…In short, women who work in the cleaning sector have a high probability of present a great loss of health. This has been found in USA (14,(27)(28)(29)(30)(31), Denmark (32)(33)(34) and Brazil (35,36) women and men (35), in hospital cleaning services. However, no studies have been found that examine the health status and psychosocial risks of female cleaning workers in Spain.…”
Section: Introductionmentioning
confidence: 70%
“…This scenario is characterized by manual and repetitive activities, little mechanical assistance, muscular effort excess, use of force and intense rhythm ( 6 ) . In addition, cleaning activities are permeated by non-ergonomic body postures that are associated with load handling tasks and frequent static muscle work in pulling, pushing, standing and walking ( 8 - 9 ) .…”
Section: Introductionmentioning
confidence: 99%